2016
DOI: 10.1111/dmcn.13201
|View full text |Cite
|
Sign up to set email alerts
|

Children with medical complexity: creating a framework for care based on the International Classification of Functioning, Disability and Health

Abstract: Children with medical complexity (CMC) comprise a growing sector of the pediatric population. They are characterized by having severe chronic multiple system conditions, functional limitations, and family needs. While CMC comprise 0.4% to 0.7% of children, they have high healthcare costs and resource utilization, and are thus a key population of interest in health reform efforts. Despite the growth in the development of complex care delivery models, there is little available information to guide the training o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 26 publications
0
28
0
2
Order By: Relevance
“…The phenomenon is also different from patient-centered medical home, an approach to providing comprehensive primary care for children, youth in developed countries, such as the US, UK (Sia, Tonniges, Osterhus, & Taba, 2004). The deeper reason behind this phenomenon that we suspect should be directly related to the complexity of pediatric specialties, the difficulty of pediatrician training, and sensitivity to pediatric treatment (Glader et al, 2016), especially the gradually developing pediatrics system in developing countries. So what the future trends in pediatric clinic services development are, continuing aggregate development or being hierarchical medical development, which brings inspiration and argument to policymakers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The phenomenon is also different from patient-centered medical home, an approach to providing comprehensive primary care for children, youth in developed countries, such as the US, UK (Sia, Tonniges, Osterhus, & Taba, 2004). The deeper reason behind this phenomenon that we suspect should be directly related to the complexity of pediatric specialties, the difficulty of pediatrician training, and sensitivity to pediatric treatment (Glader et al, 2016), especially the gradually developing pediatrics system in developing countries. So what the future trends in pediatric clinic services development are, continuing aggregate development or being hierarchical medical development, which brings inspiration and argument to policymakers.…”
Section: Discussionmentioning
confidence: 92%
“…The other burgeoning thread of research has shifted the focus to accessibility measures for different age groups, for example, highlighting age level differences, like children and older people (Neutens, 2015). Due to the particular features of pediatrics, pediatric clinic service (PCS) resources are facing high scarcity, especially in developing countries (Cohen et al, 2011;Glader, Plews-Ogan, & Agrawal, 2016). In 2016, the State Health and Family Planning Commission of China issued guidelines for strengthening the reform and development of children's medical and healthcare services1.…”
Section: Spatiotemporal Accessibility Of Healthcarementioning
confidence: 99%
“…While the care mapping process appears intuitively helpful, evaluation of the process's feasibility and clinical usefulness was missing. The clinical research team that spearheaded the definition for children with medical complexity and demonstrated the usefulness of care planning has now addressed this gap in clinical knowledge. Adams et al describe the purpose and process for developing a care map and utilize a well‐designed qualitative investigation to present evidence for the clinical feasibility and usefulness of the process …”
mentioning
confidence: 99%
“…We welcome the efforts of Glader et al 1 in applying the International Classification of Functioning, Disability and Health (ICF) to problems of medical professional team assembly, training, and other coordination of care efforts. The original release of the ICF signified an important step beyond previous models that framed care in terms of a (primary) biological health condition that could be ameliorated or exacerbated by other (secondary) factors.…”
mentioning
confidence: 99%
“…Table IV). 1 Understanding the needs of the family extends beyond immediate medical needs and should acknowledge social determinants of health. For example, the Systematized Nomenclature of Medicine -Clinical Terms (SNOMED CT) nomenclature developed in the United Kingdom incorporates information on a wide range of social determinants contributing to complexity, including family context, schooling, and housing.…”
mentioning
confidence: 99%